A cascade control approach to active suspension using pneumatic actuators. Issue 1 (8th January 2019) - Li, Yuchao; Feng, Lei; Wang, Yu
Abstract: Operators of forest machinery suffer from intensive whole body vibrations, which are big threats to their health. Therefore, it is important to investigate effective seat undercarriages and control methods for vibration reduction. This paper addresses the control problem of a novel seat undercarriage with pneumatic actuators customized for forest machinery. A two‐layer cascade control structure is developed, where the top layer consists of a group of proportional controllers to regulate the position of pneumatic actuators and the bottom layer is a sliding mode controller for force and stiffness tracking. The advantage of the sliding mode control is to achieve robust control performance with coarse system models. The paper demonstrates that the proposed control structure is better than a traditional PID controller. The robust stability of the sliding mode controller is proved by the Lyapunov's method. Experiments show its capability of reducing at least 20% amplitude of seat vibrations from 0.5 to 1 Hz.